The Impact of GB Chat on Education - A Comparative Theoretical Study - Cecile Awad, (International Journal of Computers and Informatics, 2023)
The research aimed to identify the impact of ChatGPT in education and upbringing, and to reveal the negatives and problems of using ChatGPT? How can it be addressed, the advantages of using ChatGPT, and how can ChatGPT be used to enhance education? The research was based on the comparative descriptive approach, which is based on a review of literature and research related to the research title. As ChatGPT continues to receive significant attention and is increasingly used by students, there is an urgent need to understand its impact on education and take immediate action in response to its potential threats.The current research followed the preferred rapid review and comparison of reports of systematic reviews and statistical analysis when selecting relevant articles (Moher, et al, 2009). A final search was performed using the search string “ChatGPT” in each database to search for relevant articles that included the term “ChatGPT” in their title, abstract, or keywords.Reading previous research relevant to the current research has proven that ChatGPT has contributed to the development of large language machines (LLMs) such as ChatGPT. It's an approach similar to that of Transformer and others (2022), who recently explored how GTP-3 could be used to write aspects of an academic paper about itself, with minimal human input.Launched in November 2022, the artificial intelligence-based Chat GPT bot is capable of creating coherent, information-rich, human-like responses to user input. This rapid literature review has enriched our understanding of the capabilities of Chat GPT across subject areas, how it can be used in education, and potential issues raised by researchers during the first three months of its release (i.e., from December 2022 to February 2023). A search of relevant databases and Google Scholar yielded 50 articles for content analysis (i.e., open coding, axial coding, selective coding). The results of this review also indicate that Chat GPT performance varies across subject areas, ranging from outstanding (e.g. economics) to satisfactory (e.g. programming) to unsatisfactory (e.g. mathematics). Although Chat GPT has the potential to serve as an assistant for teachers (e.g., to create course materials and provide suggestions) and a virtual tutor for students (e.g., to answer questions and facilitate collaboration), there have been challenges associated with its use (For example, generating incorrect or fake information and bypassing plagiarism detectors). Immediate action should be taken to modernize assessment methods and institutional policies in schools and universities. Teacher training and student education are also essential to respond to the impact of Chat GPT on the educational environment.The results indicate that Chat GPT has the potential to enhance teaching and learning. However, her knowledge and performance were not completely satisfactory across subject areas. Using Chat GPT also presents many potential problems, such as generating incorrect or fake information and student impersonation. Therefore, immediate action is needed to address these potential issues and improve the use of Chat GPT in education.This quick review highlights Chat GPT's diverse performance across different subject areas and its potential benefits when serving as an assistant for teachers and as a virtual tutor for students. However, its use raises various concerns, such as the generation of incorrect or fake information and the threat it poses to academic integrity. The findings of this review call for schools and universities to take immediate action to update their guidance and policies on academic integrity and plagiarism prevention. Moreover, teachers should be trained on how to use Chat GPT effectively and detect plagiarism in students. Students should also be educated about the use of Chat GPT, its limitations, and its potential impact on academic integrity.
Keywords: GB Chat; Education; Comparative Theoretical Study